2005
DOI: 10.1016/j.femsyr.2004.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Endo-polygalacturonase in wine yeasts: effect of carbon source on enzyme production

Abstract: Eight wine yeast strains of Saccharomyces sp. were tested for polygalacturonase (PGase) activity, after cultivation on various carbon sources. No strain showed any activity when grown on glucose, while five strains produced PGase in the presence of galactose and polygalacturonate. These data suggest that the PGase of wine strains is repressed by glucose and induced by galactose and polygalacturonate. The existence of the PGase gene in the wine strains and its similarity with that of the laboratory strains was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
(30 reference statements)
6
26
0
1
Order By: Relevance
“…From 61 studied wine yeast strains, the authors found 52 strains showing an amplified band corresponding to the size of the PGU1 gene and, of these strains, only 36 were able to degrade polygalacturonic acid (pectin). Radoi et al (2005) also reported that the PGU1 gene might be absent from some strains, especially OC2, KW1 and L2226 (also confirmed by PCR and Southern analyses). The authors confirmed this observation using PCR and Southern blot analyses.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…From 61 studied wine yeast strains, the authors found 52 strains showing an amplified band corresponding to the size of the PGU1 gene and, of these strains, only 36 were able to degrade polygalacturonic acid (pectin). Radoi et al (2005) also reported that the PGU1 gene might be absent from some strains, especially OC2, KW1 and L2226 (also confirmed by PCR and Southern analyses). The authors confirmed this observation using PCR and Southern blot analyses.…”
Section: Introductionmentioning
confidence: 61%
“…No amplification was obtained in 10 wine strains and in the BY4742pgu1D deletion mutant, whereas a clear band was amplified in all of the other strains screened (Fig. The absence of the PGU1 gene has already been described as a rare event (Fernandez-Gonzalez et al, 2004;Radoi et al, 2005). The absence of the PGU1 gene has already been described as a rare event (Fernandez-Gonzalez et al, 2004;Radoi et al, 2005).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Eight wine yeast strains of Saccharomyces sp. produced PG but none of them produced PL or PAL [19]. Masoud and Jespersen [20] reported that yeasts predominant during coffee processing (six strains of Pichia anomala , four strains of P. kluyveri, and two strains of Hanseniaspora uvarum ) were found to secrete PG but no PL or PE was found to be produced by the yeasts examined.…”
Section: Resultsmentioning
confidence: 99%
“…PG is produced by plants [3,4] and by microorganisms such as bacteria and fungi [5][6][7], but only a few yeast species show this ability [8,9]. In relation to their activity, PG cleaving α- [1,4]-glycosidic bonds of nonesterified galacturonic acid residues are classified as endoPG (EC 3.2.1.15) and exoPG (EC 3.2.1.67).…”
mentioning
confidence: 99%